Nursing faculty members’ perceptions of technology readiness and comfort level in implementation of high fidelity simulation teaching in the Malaysian nursing curriculum - Ahmad, Norfadzilah; Traynor, M; Johnson, L; Haughey, S (Fakultas Keperawatan Universitas Andalas, 2019)
The benefits of utilizing high-fidelity simulation (HFS) in nursing education to mimic clinical environments are well known. HFS technology has been increasingly expanding as an innovative approach to the teaching and learning process. Aims: to identify the technology readiness among Nursing Faculty Members (NFMs) in the implementation of HFS, identify the comfort levels among NFMs in utilizing HFS as a teaching method and evaluation of skills and explore NFMs’ experiences of HFS implementation in the curriculum, and challenges encountered in the Malaysian nursing curriculum. A sequential explanatory mixed-methods design was used. Phase I was the quantitative aspect using an online survey to explore the comfort levels and the technology readiness of participants. Phase II, used focus group discussions to explore in depth participant’s experiences with HFS. A total of 167 full-time NFMs participated in Phase I (66.8% response rate) and 23 participants engaged in Phase II. The majority of Malaysian NFMs respondents perceived positively the implementation of HFS in the curriculum. They valued its positive impact on learning outcomes, the student experience and the ability to simulate more complex scenarios during training. Inadequate training, lack of resources and lack of prior planning, negatively influenced the intention to use and effectively implement HFS in the curriculum. The results indicated that NFMs perceived HFS as a learning pedagogy that can improve students' learning if used effectively. They believed that to realise the potential of HFS, more support should be provided through training, the availability of necessary resources, and improved planning and organisation.